Frat Is a Phosphatidylinositol 3-Kinase/Akt-Regulated Determinant of Glycogen Synthase Kinase 3β Subcellular Localization in Pluripotent Cells - Bechard, Matthew (American Society for Microbiology, 2012)
Suppressing the activity of Gsk3β is critical for maintenance of murine pluripotent stem cells. In murine embryonic stem cells (mESCs), Gsk3β is inhibited by multiple mechanisms, including its inhibitory phosphorylation on serine 9 by protein kinase B (Akt), a major effector of the canonical phosphatidylinositol 3-kinase (PI3K) pathway. A second PI3K/Akt-regulated mechanism promotes the nuclear export of Gsk3β, thereby restricting its access to nuclear substrates such as c-myc and β-catenin. Although Gsk3β shuttles between the nucleus and cytoplasm under self-renewing conditions, its localization is primarily cytoplasmic because its rate of nuclear export exceeds its rate of nuclear import. In this report, we show that Gsk3β is exported from the nucleus in a complex with Frat. Loss of PI3K/Akt activity results in dissociation of this complex and retention of Gsk3β in the nucleus. Frat continues to shuttle between the nucleus and cytoplasm under these conditions and remains predominantly in the cytoplasm. These results indicate that Frat carries Gsk3β out of the nucleus under self-renewing conditions and that PI3K regulates this by promoting its association with Frat. These findings provide new links between PI3K/Akt signaling and regulation of Gsk3β activity by Frat, an oncogene previously shown to cooperate with Myc in tumorigenesis.